Preferred learning approaches, learning methods and learning environments: a case study of Universiti Teknologi MARA (UiTM) Sarawak, Malaysia / Senian Malie and Oriah Akir - Malie, Senian; Akir, Oriah (Universiti Teknologi MARA, Negeri Sembilan, 2012)
Employers have been critical about graduates’ lack of employable qualities. One of the steps to improve students’ quality is to understand their learning approach. Thus, the aims of this research are: to determine the impact of students’ learning approaches on their academic performance, to rank the learning methods and learning environments preferred by them.